ALJABAR C* DARI RUANG MATRIKS M_n (B(H)) - Khaerudin Saleh; Rustam Rustam; Yulinda Eliskar (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2023)
Let  be a Hilbert space. The set of  bounded operators on the Hilbert space  denotes by  can be identified as an C*-Algebra.  Let  be a Matrix vector space over the field . By using *isomorphism it will be proven that  is also a C*-algebra.